Characteristics and outcomes of L-shaped and reverse L-shaped rotator cuff tears. (1st March 2022) - Lee, Kyung Jae; Kim, Yong Tae; Choi, Minseok; Kim, Sae Hoon
Abstract : Aims: The aim of this study was to compare the characteristics and outcomes of L-shaped and reverse L-shaped rotator cuff tears. Methods: A total of 82 shoulders (81 patients) after arthroscopic rotator cuff repair were retrospectively enrolled. The mean age of the patients was 62 years (SD 6), 33 shoulders (40.2%) were in male patients, and 57 shoulders (69.5%) were the right shoulder. Of these, 36 shoulders had an L-shaped tear (group L) and 46 had a reverse L-shaped tear (group RL). Both groups were compared regarding characteristics, pre- and postoperative pain, and functional outcomes. Muscle status was assessed by preoperative MRI, and re-tear rates by postoperative ultrasonography or MRI. Results: Patients in group RL were significantly older than in group L (p = 0.008), and group RL was significantly associated with female sex (odds ratio 2.5 (95% confidence interval 1.03 to 6.32); p = 0.041). Mean postoperative pain visual analogue scale (VAS) score was significantly greater (group L = 0.8 (SD 1.5), group RL = 1.7 (SD 2.2); p = 0.033) and mean postoperative American Shoulder and Elbow Surgeons (ASES) score was significantly lower in group RL than group L (group L = 91.4 (SD 13.1), group RL = 83.8 (SD 17.9); p = 0.028). However, postoperative mean VAS for pain and ASES score were not lower than the patient-acceptable symptom state scores. Mean retracted tear length was significantly larger in group L (group L = 24.6 mm (SD 6.5), group RL = 20.0 mm (SD 6.8); p = 0.003). Overall re-tear rate for 82 tears was 11.0% (nine shoulders), and re-tear rates in group L and RL were similar at 11.1% (four shoulders) and 10.9% (five shoulders), respectively (p = 1.000). No significant intergroup difference was found for fatty degeneration (FD) or muscle atrophy. Within group L, postoperative FD grades of supraspinatus and subscapularis worsened significantly (p = 0.034 and p = 0.008, respectively). Mean postoperative pain VAS (male = 1.2 (SD 1.8), female = 1.3 (SD 2.0)) and ASES scores (male = 88.7 (SD 15.5), female = 86.0 (SD 16.8)) were similar in male and female patients (p = 0.700 and p = 0.475, respectively). Regression analysis showed age was not a prognostic factor of postoperative pain VAS or ASES scores (p = 0.188 and p = 0.150, respectively). Conclusion: Older age and female sex were associated with reverse L-shaped tears. Although the postoperative functional outcomes of patients with reverse L-shaped tears were satisfactory, the clinical scores were poorer than those of patients with L-shaped tears. Surgeons should be aware of the differences in clinical outcome between L-shaped and reverse L-shaped rotator cuff tears. Cite this article: Bone Joint J 2022;104-B(3):394–400.